Concepts for Sustainable Landscape Mosaics - Tina McIntyre; Rachel Gutner; Sandra Wilson (EDIS)
This new 9-page publication of the UF/IFAS Environmental Horticulture Department is for Florida homeowners, residential and commercial property managers, and landscape architects interested in creating aesthetically pleasing landscapes and to help individuals choose the right plant for the right place. Written by Tina McIntyre, Rachel Gutner, and Sandra Wilson.